Biological, dietetic and pharmacological properties of vitamin B9 - Siatka, Tomáš; Mát'uš, Marek; Moravcová, Monika; Harčárová, Patrícia; Lomozová, Zuzana; Matoušová, Kateřina; Suwanvecho, Chaweewan; Krčmová, Lenka Kujovská; Mladěnka, Přemysl (NPJ science of food, 2025)
Humans must obtain vitamin B9 (folate) from plant-based diet. The sources as well as the effect of food processing are discussed in detail. Industrial production, fortification and biofortification, kinetics, and physiological role in humans are described. As folate deficiency leads to several pathological states, current opinions toward prevention through fortification are discussed. Claimed risks of increased folate intake are mentioned as well as analytical ways for measurement of folate.